2020
DOI: 10.15561/20755279.2020.0504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varied packages of plyometric training on selected motor ability components among university students

Abstract: Background and Study Aim. The main focus of the study was to examine the effect of varied packages of plyometric training on speed, leg explosive power, and muscular endurance among university students. Material and Methods. Sixty subjects (age= 21.37+1.40) were divided into two groups namely, Control Group (CG, n=15) and Experimental Group (EG, n=45). The EG was further divided into three different groups based on the different training packages such as Low, Medium, and High-Intensity plyometric trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Athletes undertake various physical activities to strengthen their technical and physical potential (1) .In this regard, plyometric exercises positively affect physical fitness https://www.indjst.org/ indicators such as muscular power, strength endurance, speed, and flexibility while being safe (with no documented injuries) (2)(3)(4)(5)(6)(7)(8) These exercises can help improve muscle function by allowing muscles to stretch quickly while making an explosive muscle movement (9) . Plyometrics use the stretch-shortening cycle, which involves two quick, alternating movements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes undertake various physical activities to strengthen their technical and physical potential (1) .In this regard, plyometric exercises positively affect physical fitness https://www.indjst.org/ indicators such as muscular power, strength endurance, speed, and flexibility while being safe (with no documented injuries) (2)(3)(4)(5)(6)(7)(8) These exercises can help improve muscle function by allowing muscles to stretch quickly while making an explosive muscle movement (9) . Plyometrics use the stretch-shortening cycle, which involves two quick, alternating movements.…”
Section: Introductionmentioning
confidence: 99%
“…In an exhaustive meta-analysis of studies performed on male and female volleyball players, Ramirez-Campillo et al (30) showed that plyometric jump training is safe and effective in improving physical fitness. Khan et al (31) examined the effect of plyometric training on various physical aspects of university students and reported significant development in their improving motor ability. Extensive research has also proven the positive effects of yoga in multiple sports, including volleyball.…”
Section: Introductionmentioning
confidence: 99%